Ciência, raça e nação: a obra de Gobineau e a produção do discurso racialista no Brasil (1850-1888) - Lissker, Beatriz (2025)
The aim of this dissertation is to analyze the construction of the racialist discourse of Joseph Arthur de Gobineau (1816 - 1882), a 19th-century French intellectual and diplomat, investigating how his theoretical postulates resonated in Brazil, shaping a specific national project. In his most renowned work, Essai sur l’inégalité des races humaines (1853-1855), Gobineau explores the causes behind the decline of once-vigorous civilizations and identifies racial miscegenation as the imperative of degeneration. Count Gobineau spent 14 months in Brazil between 1869 and 1870 on a diplomatic mission, during which he tested his theories by observing an intensely mixed society whose ethnic “barbarism” pointed to a catastrophic prognosis. This study examines Gobineau's interpretation of Brazil, assessing the extent to which his discourse, particularly from the 1850s onwards, provided crucial foundations for constructing a nationalist imaginary and practices centered on the idea of race. At the heart of this process, science and race became the cornerstones upon which the Brazilian intellectual elite projected the idea of a modern nation